État, droits et pouvoir - Fabrizio Cantelli (Sociologies, 2023)
It is difficult to continue to separate anthropological conceptions of the individual (responsible, capable, autonomous, fragile, vulnerable…) and the evolution of the State, law and public services. In such a context, and in the face of questions about what the State is and what it does today, the human sciences are rich thanks to the sociological work and concepts of Jean-Louis Genard. This contribution traces the path taken by Jean-Louis Genard’s sociology on the joint mutations of the state, rights, power, capacity, the individual and administration. It begins by examining the current reconfigurations of public action (management, participation, expertise, etc.), in close connection with an examination of anthropological forms (responsibility, capacity, autonomy, etc.). Secondly, we describe the main lines of the book entitled Pouvoir et ne pas pouvoir (IES, coll. “Le geste social”), written with Jean-Louis Genard before his death, whose aim is to enrich classical conceptions of power and the state. This contribution can be read as a gesture to be extended, a call to be passed on, an invitation to continue research on the State, based on a decompartmentalized approach and a spirit of critical dialogue and free examination.